2012
DOI: 10.1016/j.jtcvs.2012.06.030
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of microRNA sequence polymorphisms on the recurrence of patients with completely resected non–small cell lung cancer

Abstract: Our findings suggest that polymorphisms in the rs2910164 of miR-146a and the rs11614913 of miR-196a2 are associated with prognosis in patients with completely resected NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 25 publications
1
54
0
Order By: Relevance
“…MiR-27a expression is up-regulated in breast cancer (41) but down-regulated in colorectal cancer and oral squamous carcinoma and expressed at low levels in both the serum and plasma of NSCLC patients (26,42,43). It is also reported that an reference single nucleotide polymorphism (rs)895819 SNP was found in precursor miRNA (premiR)-27a in NSCLC patients (44). As shown in Figs.…”
Section: Discussionmentioning
confidence: 85%
“…MiR-27a expression is up-regulated in breast cancer (41) but down-regulated in colorectal cancer and oral squamous carcinoma and expressed at low levels in both the serum and plasma of NSCLC patients (26,42,43). It is also reported that an reference single nucleotide polymorphism (rs)895819 SNP was found in precursor miRNA (premiR)-27a in NSCLC patients (44). As shown in Figs.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, Yoon et al reported that rs895819 of miR-27a was not associated with prognosis in patients with completely resected NSCLC in Korean population (Yoon et al, 2012). A study conducted by Xu et al suggested that miR-27a rs895819 polymorphism might influence NSCLC patients' clinical outcome (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rs895819, a SNP locus located in the terminal loop of pre-miR-27a, was reported to be significantly associated with the risk of gastric and cervical cancers (Sun et al, 2010;Xiong et al, 2014). However, there is no study reported the association between the locus and the risk of NSCLC, and prognostic results between them remain elusive (Xu et al, 2013;Yoon et al, 2012). Therefore, in order to address the role of rs895819 in the risk and prognosis of NSCLC, we genotyped the locus in 560 NSCLC patients and 568 healthy check-up individuals and followed-up the cases to examined the possible association between them.…”
Section: Rs895819 Within Mir-27a Might Be Involved In Development Of mentioning
confidence: 99%
“…Out of the Twenty-five, seven articles were pooled analysis, commentary and review papers (Wang et al, 2012;Yang and Burwinkel, 2012;Ma et al, 2013;Wang et al, 2013;Xu et al, 2013b;Zhong et al, 2013;Chen et al, 2014), and four reports were cancer biology experimental studies (Hirota et al, 2012;Jahid et al, 2012;Zanetti et al, 2012;Yuan et al, 2013). Three studies were excluded given that they did not include controls (Yoon et al, 2012;Xu et al, 2013a), or reported non-cancer disease (Song et al, 2013). We also included five eligible articles by manual searching (Li, 2011;Zhang, 2011;Zhang, 2012;Xu et al, 2013b;Kupcinskas et al, 2014), in which the study by Li et al included two independent case-control studies (Li, 2011) and the pooled analysis by Xu et al included one unpublished paper with efficient case-control study data (Xu et al, 2013b).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%